Eurobarometer 43.0+43.1: Drug abuse and AIDS, March-May 1995 - Reif, Karlheinz; Marlier, Eric; Commission of the European Communities (Commission of the European Communities, 1997)
This dataset merges the responses to identical questions from two waves of Eurobarometer surveys, Eurobarometer 43.0, March-April 1995 (SND 0507) and Eurobarometer 43.1: International Trade and Radiation Protection, April-May 1995 (SND 0508). These surveys focused on drug use and AIDS. Demographic and other background information was gathered on the number of people residing in the home, size of locality, household income, and region of residence, as well as the respondent's age, sex, marital status, age when completed education, occupation, previous occupation, and left-right political self-placement.

Detta dataset för samman svaren på identiska frågor från två Eurobarometerundersökningar, Eurobarometer 43.0, March-April 1995 (SND 0507) och Eurobarometer 43.1, April-May 1995 (SND 0508). Dessa frågor rörde droganvändning och AIDS. Demografisk information samlades in gällande antalet personer i hushållet, ortsstorlek, hushållsinkomst och tillhörande region. Annan bakgrundsinformation som samlades in var respondentens ålder, kön, civilstånd, ålder vid avslutad utbildning, nuvarande och tidigare yrken och självplacering på den politiska vänster-högerskalan.
Eurobarometer 43.0+43.1: Drug abuse and AIDS, March-May 1995
EB 43.0+43.1
Keywords: drinking behaviour; alkoholvanor; smoking; rökning; drug abuse; drogmissbruk och medicinmissbruk; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Social Sciences; Samhällsvetenskap; Diet and nutrition; Kost och näring